Sahli's Method and Reality: Revealing Weaknesses in Determining Hemoglobin Levels in Pregnant Women - Ira Jayanti; Muhammad Ihza Lisan Shidqi; Yanti Sunaidi; Yampa Eksa Daidella Ghilari; Antoni Aldo Danendra Sawal (PT.Mantaya Idea Batara, 2026)
Background: Anemia among pregnant women remains a significant health concern, increasing the risk of maternal and perinatal complications. Accurate hemoglobin (Hb) testing is therefore critical in antenatal care. This study analyzed the incidence of anemia and assessed the agreement between Hb measurements obtained using the Sahli Method and those from a Hematology Analyzer among third-trimester pregnant women in Makassar City Methods: An analytical, observational, cross-sectional design was employed, involving 112 purposively sampled pregnant women. Hb levels were measured using both the Sahli Method and the Hematology Analyzer, the latter serving as the reference standard. Results: indicated that 70 participants (62.5%) were classified as anemic, while 42 participants (37.5%) exhibited discrepancies in Sahli Method results. The mean Hb level measured by the Sahli Method was 10.8 g/dL, compared to 11.6 g/dL by the Hematology Analyzer, with a mean difference of 0.8 g/dL, which was statistically significant (p<0.05). Although a strong correlation was observed between the two methods, the Sahli Method's inaccuracy may result in misdiagnosis. Conclusion: The findings suggest that the Sahli Method is suboptimal for definitive anemia diagnosis in pregnant women and should be supplemented by more accurate testing to ensure appropriate clinical interventions.